Robotic Adrenalectomy: An Initial Experience in a Turkish Regional Hospital - Ayhan Erdemir; Kemal Rasa (Frontiers in Surgery, 2022)
BackgroundDue to the technical advantages and the convenience it provides to surgeons, “robotic adrenalectomy” is a widely used procedure for adrenal surgeries. In this study, we aim to evaluate our robotic adrenalectomy experience and delineate the factors that have a substantial impact on surgical outcomes.MethodsSuccessive 0 transperitoneal robotic operations using the daVinci SI® platform were grouped according to the surgery side, malignant or benign pathologies, for adenoma or non-adenoma lesions, tumor size of less than 4 cm or above, body mass index below or above 30 kg/m2, and with or without laparotomy history. Groups were compared in terms of duration of the operations, amount of bleeding, and the duration of hospitalization.ResultsMorbidity developed in 5 patients (16.6%), and no mortality was observed. We had only one conversion to perform open surgery (3.3%). Operations performed for adenoma significantly last longer when compared with the non-adenoma group (p < 0.05). In the malignant group, the amount of bleeding during surgery was found to be significantly higher (p < 0.05). The blood loss during the surgery was also found to be higher in the adenoma group than in the non-adenoma match (p < 0.05). Phenomenally, operative blood loss was found to be lesser in the bigger tumor size group (>4 cm) than in the smaller size group (p < 0.05).ConclusionOur results corroborate that robotic adrenalectomy may be more challenging for malignant pathologies and adenomas, but we can claim that it is an effective and safe option for all adrenal gland pathologies.